Preparation of dense ScSZ thin films by plasma spraying with densified ScSZ powders. (26th February 2021) - Yuan, Kang; Song, Chen; Chen, Gang; Xu, Zhenyuan; Peng, Haoran; Lu, Xiaoliang; Ji, Xiaojuan
Abstract: Low-pressure plasma spray (LPPS) technology was applied to make scania-stabilized zirconia (ScSZ) thin films for solid oxide fuel cell (SOFC). Agglomerated ScSZ powders and densified ScSZ powders sintered at high temperature were synthesized and sprayed to make dense ScSZ thin films in the LPPS processes. SEM results indicate that the densified ScSZ powders can be easier molten in plasma stream to form more uniform and denser thin films. The influence of spraying parameters on the microstructure of the films was investigated. It is found that longer spraying distance was beneficial to the melting of the flying powders to make high-quality thin films. The ionic conductivity of the thin film (about 20 μm thick) was about 0.025 S/cm measured at 700 °C. A half-cell sample was made via air plasma spray process by using the densified ScSZ powder. The result indicated that a denser and thinner ScSZ should be made for higher electrochemical property. Highlights: Low-pressure plasma spray technology is used to make ScSZ thin film. Agglomerated and sintered powders were synthesized and sprayed for comparison. The sintered powders were easier molten to form denser thin films. Longer spraying distance was beneficial for making higher-quality thin films.